Gap-Graded Mixes - Ramírez Castro, Laura (2025)
This project aims to analyze the behavior of gap-graded mixes using commonly used binders and aggregates in Costa Rica, with the goal of developing specifications focused on designing and constructing mixes that are more resistant to rutting and offer greater durability. To achieve this, work was carried out on selecting the optimal gradation, and Marshall mix designs as well as Superpave mix designs were developed. Laboratory-scale rutting was analyzed using the Georgia Loaded Wheel Tester, resilient modulus was measured through indirect tensile testing, and moisture sensitivity was evaluated using immersion-compression tests (retained tensile strength and uniaxial compression). It was found that a lack of aggregate cubicity can negatively impact the performance of this type of mix, as it prevents achieving effective stone-on-stone contact. Mixes produced with cellulose fiber exhibited greater deformation compared to mixes without cellulose fiber. Moreover, both dry and conditioned strength values were lower in cellulose fiber mixes compared to those without cellulose fiber.